2018
DOI: 10.1002/ptr.6103
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol and human health: A comprehensive review

Abstract: Carvacrol (CV) is a phenolic monoterpenoid found in essential oils of oregano (Origanum vulgare), thyme (Thymus vulgaris), pepperwort (Lepidium flavum), wild bergamot (Citrus aurantium bergamia), and other plants. Carvacrol possesses a wide range of bioactivities putatively useful for clinical applications such antimicrobial, antioxidant, and anticancer activities. Carvacrol antimicrobial activity is higher than that of other volatile compounds present in essential oils due to the presence of the free hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
261
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 438 publications
(315 citation statements)
references
References 127 publications
(202 reference statements)
5
261
1
4
Order By: Relevance
“…As is known, phenolic compounds show good antioxidant activity in the hydrophilic and hydrophobic media. Carvacrol is a phenolic monoterpenoid found in the essential oils of some plants . The antioxidant potential of carvacrol is therefore higher than that of other volatile compounds present in essential oils through the presence of the free hydroxyl group and the phenol moiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, phenolic compounds show good antioxidant activity in the hydrophilic and hydrophobic media. Carvacrol is a phenolic monoterpenoid found in the essential oils of some plants . The antioxidant potential of carvacrol is therefore higher than that of other volatile compounds present in essential oils through the presence of the free hydroxyl group and the phenol moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Carvacrol is a phenolic monoterpenoid found in the essential oils of some plants. 35 The antioxidant potential of carvacrol is therefore higher than that of other volatile compounds present in essential oils through the presence of the free hydroxyl group and the phenol moiety. In addition, Ozturk reported that γ-terpinene also exhibited similar activity to those of phenolic compounds, 5 and therefore the antioxidant activity of both essential oils could be attributed to the presence of these components.…”
Section: Antioxidant Activity Of the Essential Oilsmentioning
confidence: 99%
“…Herbal extracts also present some interesting features. Oreganum vulgarae and its principal compounds, carvacrol, as well as Cymbopogon flexuosus, that is, lemongrass, can have positive effects on behavior and emotions (Amiresmaeili, Roohollahi, Mostafavi, & Askari, 2018;Blanco, Costa, Freire, Santos, & Costa, 2009;Costa et al, 2011;Jugl-Chizzola et al, 2006;Mechan et al, 2011;Pires et al, 2013;Sharifi-Rad et al, 2018;Zotti et al, 2013). In this study, we compared two food ingredients with putative orexigenic and hedonic outcomes: ingredient A, derived from C. sinensis extracts, and ingredient B, a combination of O. vulgarae and C. flexuosus extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the volatile compounds, essential oils (EOs) are considered as potential medicinal agents (Salehi et al, ; J. Sharifi‐Rad, Sureda, et al, ; M. Sharifi‐Rad, Varoni, et al, ; M. Sharifi‐Rad et al, ; Yu et al, ). The EOs from Echinacea plants can be obtained from different parts of the plants, such as roots, leaves, flowers, and aerial parts, and with different yields (Mazza & Cottrell, ).…”
Section: Chemical Composition Of Essential Oils Obtained From Echinacmentioning
confidence: 99%